Toxic Positivity Content Uploads on Instagram in Encouraging the Growth of Hustle Culture Gen Z - Zainal Abidin Achmad; Putri Nada Camilia Lubna (JOSAR (Journal of Students Academic Research), 2023)
Exposure to toxic positivity content uploads on Instagram during the pandemic has motivated some Gen Z to act hustle. This research uses a virtual ethnographic approach to see digital interactions, media-making processes, and individual motivation in interpreting toxic positivity content on Instagram, which can build Gen Z Surabaya to act hustle. This research shows that there are factors in the scope of friendship, frame of reference, field experience, to family in building motivation to act hustle through consumed toxic positivity content. It can be concluded that Instagram is a medium for the media-making process of turning content into an action that can affect the lives of its users.